QT dispersion increases during intubation in patients with coronary artery disease - FAK, ALİ SERDAR (CHURCHILL LIVINGSTONE INC MEDICAL PUBLISHERS, 2003)
Anesthetic drugs have been shown to increase QT interval, however data regarding their effects on QT dispersion (QTd) are scarce, especially in patients with Coronary artery disease (CAD). We tested whether induction of Anesthesia with thiopental and etomidate would increase QTd in patients with CAD. Thirty American Society of Anesthesiologists (ASA) physical status I-II patients without CAD were randomly allocated to groups I (n = 15) and II (n = 15) and 30 ASA physical status III patients with CAD were randomly allocated to groups III (n = 15) and IV (n=15). Anesthesia was induced with thiopental 5-7 mg/kg IV in groups I and III and with etomidate 0.2-0.3 mg/kg IV in groups H and IV. Endotracheal intubation was facilitated with vecuronium bromide 0.1 mg/kg IV. Twelve-lead electrocardiogram (ECG) was recorded in all patients at baseline (ECG(1)), 1 min after the induction agent (ECG(2)), 1 min (ECG,) and 5 min (ECG(4)) after intubation. Anesthesia was maintained with isoflurane and nitrous oxide in 34 % oxygen after ECG, recording. QTd and corrected QT dispersion (QTcd) were calculated. In patients with CAD induced with thiopental, QT dispersion increased significantly during the intubation period compared with baseline (from 43.0 +/- 25.6 ms to 69.2 +/- 25.3 ms; P < .01). Likewise, QT dispersion also increased during intubation in patients with CAD induced with etomidate (from 41.5 +/- 17.2 ms to 80.0 +/- 33.6 ms; P < .001). There was no increase in QT dispersion in patients without known CAD. QT dispersion seems to be increased during the intubation period in patients with CAD regardless of the induction agents used.
Keywords: QT dispersion; coronary artery disease; anesthetic induction agents; thiopental-etomidate; VENTRICULAR REPOLARIZATION; INTERVAL; ANESTHESIA; ISOFLURANE; PROLONGATION; HALOTHANE; DEATH